2021
DOI: 10.1177/20587384211009342
|View full text |Cite
|
Sign up to set email alerts
|

Chidamide induces long-term remission in rare subcutaneous panniculitis-like T-cell lymphoma: An unusual case report and literature review

Abstract: Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a rare primary cutaneous lymphoma composed of CD8+ cytotoxic T-cell that is primarily localized in the subcutaneous tissue. No standard treatments are currently available for SPTCL due to its rarity. Chemotherapy, radiotherapy, immunosuppressive agents, and hematopoietic stem cell transplantation (HSCT) have been used frequently, however, the effects of these treatment approaches remain controversial. In this report, we present an unusual case of SPTCL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Only 1 case has reported that Chidamide performs well in the treatment of refractory SPTCL. [7] This case we report is a refractory/recurrent SPTCL, which achieved continuous remission after the addition of Chidamide on the basis of CHOP plus auto-HSCT, once again confirming the efficacy of Chidamide in SPTCL. However, more particularly, this case was accompanied by a mutation in ARID1A, indicating that the good efficacy of Chidamide in this SPTCL case may be related to the ARID1A mutation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Only 1 case has reported that Chidamide performs well in the treatment of refractory SPTCL. [7] This case we report is a refractory/recurrent SPTCL, which achieved continuous remission after the addition of Chidamide on the basis of CHOP plus auto-HSCT, once again confirming the efficacy of Chidamide in SPTCL. However, more particularly, this case was accompanied by a mutation in ARID1A, indicating that the good efficacy of Chidamide in this SPTCL case may be related to the ARID1A mutation.…”
Section: Discussionsupporting
confidence: 72%
“…Only 1 case has reported that Chidamide performs well in the treatment of refractory SPTCL. [ 7 ] Nevertheless, it is still currently unknown whether all SPTCL patients can be routinely treated with Chidamide and whether there are molecular markers which can predict the efficacy of Chidamide on SPTCL.…”
Section: Introductionmentioning
confidence: 99%
“…53 Chidamide, a histone deacetylase inhibitor, may play a role in refractory SPTCL case, proposed in a case report in China. 54 Histone deacetylase inhibitors could modulate gene expression via hyperacetylation of histones and change nonhistone proteins via regulation at the epigenetic and posttranslational modification levels. 55 Another kind of histone deacetylase inhibitor, Romidepsin, was also utilized in the treatment of one refractory SPTCL in Chicago by targeting PI3k/AKT/mTOR and the Jak/STAT pathways.…”
Section: Sptcl With Hpsmentioning
confidence: 99%
“…Chidamide, a histone deacetylase inhibitor, may play a role in refractory SPTCL case, proposed in a case report in China 54 . Histone deacetylase inhibitors could modulate gene expression via hyperacetylation of histones and change nonhistone proteins via regulation at the epigenetic and posttranslational modification levels 55 .…”
Section: Case Presentationmentioning
confidence: 99%
“…Our case differs from these prior studies in that our patient did not have HLH, failed all initial immunosuppressive therapy, and did not have relapsed SPTCL. Another report demonstrated complete remission of systemic SPTCL with chidamide, a different HDAC inhibitor [15]. However, chidamide was used in combination with chemotherapy to achieve remission, so it is unknown whether the positive clinical response was due solely to the HDAC inhibitor.…”
Section: Case Reports In Oncologymentioning
confidence: 99%